Feasibility of engaging parents attending an adult weight management programme with child weight management support: a mixed methods study - Russell Jago; Julian PH Shield; Aidan Searle; Ruth Mears; Deborah Sharp (BMJ Paediatrics Open)
Objective To explore whether parents’ attendance at a commercial adult weight management programme (WMP) offers an opportunity to identify and signpost families to child weight management support, if appropriate to a child’s weight status.Design Mixed methods study including a cross-sectional online survey and semistructured telephone interviews.Setting and participants Parents attending Slimming World (UK-based adult commercial WMP), with one or more children aged 5–11 years, were invited to take part. There were 396 survey and 18 telephone interview participants.Results Most parents (78%) attending the adult WMP and worried about their child’s weight were receptive to being offered support for their child. Nearly all (98%) of these parents were happy for the adult WMP to signpost to this support. Nearly half of parents (47%, n=122/262) not worried about their child’s weight were still interested in a child height and weight check. The preferred intervention format and delivery possibilities differed among parents, with ‘no-one size fits all’, while recognising that change takes time, and weekly sessions may be too frequent. Parents were clear that the focus of support should be on healthy lifestyle not weight. Many parents felt a parent ‘peer support’ group would be helpful.Conclusions Parents actively addressing their own weight, through an adult WMP, are receptive to being offered and signposted to support for their child, where they have concerns about their child’s weight. These findings support a new referral pathway into child weight management services, through parents attending an adult WMP.